Intramyocardial dissecting hematoma: fatal complication of reperfusion damage in myocardial infarction - an autopsy case report - Hrudka, Jan (Cardiovascular pathology, 2020)
Intramyocardial dissection or intramyocardial dissecting hematoma is uncommon complication either of myocardial infarction or severe thoracic injury. Intramyocardial dissecting hematoma is caused by intersecting bleeding between the layers of myocardial fibers. In contrast to cardiac rupture, the myocardial wall maintains its integrity. In this paper, we present a case of patient suffering with ischemic heart disease, reporting worsening chest pain and dyspnea 2 months after autovenous graft bypass surgery. The coronary angiography revealed severe stenosis of the autovenous graft, which was treated by stent implantation. Three hours after intervention, the patient showed signs of cardiogenic shock with clinical suspicion of heart tamponade because of ventricular wall rupture. The patient died despite the surgical drainage of the hematoma and blood transfusions. In the necropsy, the large intramyocardial dissecting hematoma in the very superficial layer of the left ventricular myocardium was found, accompanied with very small extent of necrotic myocardium in the neighborhood of the intramyocardial dissecting hematoma. The prevailing majority of the left ventricle thickness was vital. The lack of developed transmural infarction in our case leads us to hypothesis that the increased intravascular pressure during the reperfusion is the main contributor to the intramyocardial dissecting hematoma development, together with reduced biomechanical resistance of the capillaries affected by chronic ischemia.
Keywords: senioři nad 80 let; pitva; hematom; Graft Occlusion, Vascular; mužské pohlaví; infarkt myokardu; Myocardial Reperfusion Injury; příčina smrti; Hematoma; Fatal Outcome; koronární bypass; Myocardial Infarction; Coronary Artery Bypass; reperfuzní poškození myokardu; Aged, 80 and over; myokard; Humans; Myocardium; stenty; koronární angioplastika; Percutaneous Coronary Intervention; Stents; okluze cévního štěpu; Cause of Death; fatální výsledek; lidé; Male; Autopsy